Application of Wroclaw Taxonomy in Classification of GNSS Interferences in Business Use - Dariusz ZMYSŁOWSKI (Communications of International Proceedings, 2021)
The purpose of this article is to present a proposal of the Wrocław taxonomy application to identify and classify disruptors of GNSS systems functioning. Modern economy areas that may be susceptible to the harmful and destructive influence of intentional disturbance in the form of jamming and spoofing attacks were presented. The idea of Wroclaw taxonomy used to increase knowledge of received and preliminarily recognized disruptions was described.
Keywords: GNSS; use of GNSS; interferences of GNSS; classification of interferences cluster method; Wroclaw taxonomy; matrix of parameters; dendrite; diagnostic variables.